Anadyrskīĭ limanʺ i ustʹe ri︠e︡ki Anadyrʹ vʺ Beringovom mori︠e︡ / Sostavleno vʺ 1900 g. - Soviet Union. Gidrograficheskoe upravlenie (Leningrad : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenie SSSR; [Ленинград] : Морское министерство, Главное гидрографическое управление СССР, 1925)
Malai︠a︡ korrekt. IX-1914 g. -- Bolʹsh. korr. IX-1923 g. Pechatano vʺ 1925 g; Малая коррект. IX-1914 г. -- Больш. корр. IX-1923 г. Печатано въ 1925 г.; Relief shown by hachures. Depths shown by soundings and isolines.; Main title translation: Anadyr estuary and the mouth of the Anadyr river in the Bering Sea.; Top margin title translation: Eastern Sea, Bering Sea.; Inclues note, 2 illustrated views of coastlines and a list of navigational coordinate points.; "Masshtabʺ 1/182616 ili 2,5 mili vʺ di︠u︡ĭmi︠e︡" = Scale 1/182616 or 2.5 miles in 1 inch.; Greenwich meridian.; "No. 560" -- margins Color; 1:182,616